Cardiac dysfunction in cancer survivors unmasked during exercise. (30th January 2017) - Kearney, Maria C.; Gallop‐Evans, Eve; Cockcroft, John R.; Stöhr, Eric J.; Lee, Eveline; Backx, Karianne; Haykowsky, Mark; Yousef, Zaheer; Shave, Rob
Abstract: Background: The cardiac dysfunction associated with anthracycline‐based chemotherapy cancer treatment can exist subclinically for decades before overt presentation. Stress echocardiography, the measurement of left ventricular (LV) deformation and arterial haemodynamic evaluation, has separately been used to identify subclinical cardiovascular (CV) dysfunction in several patient groups including those with hypertension and diabetes. The purpose of the present cross‐sectional study was to determine whether the combination of these techniques could be used to improve the characterisation of subclinical CV dysfunction in long‐term cancer survivors previously treated with anthracyclines. Materials and methods: Thirteen long‐term cancer survivors (36 ± 10 years) with prior anthracycline exposure (11 ± 8 years posttreatment) and 13 age‐matched controls were recruited. Left ventricular structure, function and deformation were assessed using echocardiography. Augmentation index was used to quantify arterial haemodynamic load and was measured using applanation tonometry. Measurements were taken at rest and during two stages of low‐intensity incremental cycling. Results: At rest, both groups had comparable global LV systolic, diastolic and arterial function (all P > 0·05); however, longitudinal deformation was significantly lower in cancer survivors (−18 ± 2 vs. −20 ± 2, P < 0·05). During exercise, this difference between groups persisted and further differences were uncovered with significantly lower apical circumferential deformation in the cancer survivors (−24 ± 5 vs. −29 ± 5, −29 ± 5 vs. 35 ± 8 for first and second stage of exercise respectively, both P < 0·05). Conclusion: In contrast to resting echocardiography, the measurement of LV deformation at rest and during exercise provides a more comprehensive characterisation of subclinical LV dysfunction. Larger studies are required to determine the clinical relevance of these preliminary findings.